The management and operation of systems of physical education in the secondary schools of foreign countries - N. V. Kandaurova; I. V. Kulkova (Путеводитель предпринимателя)
The article provides a theoretical analysis of foreign experience in the development of school sports, revealed features of the content of educational programs of physical education and school sports system functioning in developed foreign countries, in the United States. China, UK, Germany, Austria, Finland, France, Italy and Japan.